Fluid balance, carbohydrate ingestion, and body temperature during men`s stage-race cycling in temperate environmental conditions - Ross, M. L.; Stephens, B.; Abbiss, C. R.; Martin, D. T.; Laursen, P. B.; Burke, L. M. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To observe voluntary fluid and carbohydrate intakes and thermoregulatory characteristics of road cyclists during 2 multiday, multiple-stage races in temperate conditions. Methods: Ten internationally competitive male cyclists competed in 2 stage races (2009 Tour of Gippsland, T1, n = 5; 2010 Tour of Geelong, T2, n = 5) in temperate conditions (13.2-15.8°C; 54-80% relative humidity). Body mass (BM) was recorded immediately before and after each stage. Peak gastrointestinal temperature (TGI peak) was recorded throughout each stage. Cyclists recalled the types and volumes of fluid and food consumed throughout each stage. Results: Although fluid intake varied according to the race format, there were strong correlations between fluid intake and distance across all formats of racing, in both tours (r = .82, r = .92). Within a stage, the relationship between finishing time and fluid intake was trivial. Mean BM change over a stage was 1.3%, with losses >2% BM occurring on 5 out of 43 measured occasions and the fastest competitors incurring lower BM changes. Most subjects consumed carbohydrate at rates that met the new guidelines (30-60 g/h for 2-3 h, ~90 g/h for >3 h), based on event duration. There were consistent observations of TGI peak >39°C during stages of T1 (67%) and T2 (73%) despite temperate environmental conditions. Conclusion: This study captured novel effects of high-intensity stage racing in temperate environmental conditions. In these conditions, cyclists were generally able to find opportunities to consume fluid and carbohydrate to meet current guidelines. We consistently observed high TGI peak, which merits further investigation.